PENGUATAN PENDIDIKAN KARAKTER PADA ANAK SEKOLAH DASAR - Lastri Winarsih; Warsono Warsono; Nanik Setyowati (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
Character education in elementary school children needs strengthening. This study aims to conduct a literature review on strengthening character education in elementary school children. This research uses qualitative research with the literature review method. Selection of literature using techniques based on keywords strengthening character education in elementary school students. In this study, the literature comes from Google Scholar with a publication limit of the last 10 years. The literature review study technique in this study used a synthetic matrix based on reference sources, methods, interventions, and findings. The results showed that 10 national journals conducted literature reviews. Character education in elementary school children needs strengthening. Strengthening can be done in learning materials; school rules, science competitions between students, awards for outstanding students, commemoration of national day, worship practices and spiritual guidance, activities; there is a talent and music class.